Devitalized biological vascular grafts: 3 years follow up - Byzov, D.V.; Чиж, М.О.; Shevchenko, E.V.; Mikhaylova, I.P.; Sandomirsky, B.P. (Cardiovasc Res. 2014. Vol. 103 (suppl. 1): S143., 2014)
Devitalized biological vascular grafts: 3 years follow up
Byzov D., Chizh N., Shevchenko E., Mikhaylova I., Sandomirsky B.. Devitalized biological vascular grafts: 3 years follow up. Cardiovasc Res. 2014. Vol. 103 (suppl. 1): S143. doi:10.1093/cvr/cvu098
Keywords: vascular grafts